If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 83 + -5y = 3 Solving 83 + -5y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-83' to each side of the equation. 83 + -83 + -5y = 3 + -83 Combine like terms: 83 + -83 = 0 0 + -5y = 3 + -83 -5y = 3 + -83 Combine like terms: 3 + -83 = -80 -5y = -80 Divide each side by '-5'. y = 16 Simplifying y = 16
| 8-6x=4x+49 | | x/2+2=15 | | 14x-6x=72 | | log(5x)=log(x-1)+1 | | 4(x+4)=4(x+15) | | -(x+4)=-2(3x+16) | | 6x-y-5=0 | | 6(x+5)=6(x+11) | | 45=-5x | | 4(4x+3)=15x+10 | | 4x+2+3x=5x+14+x | | a^3+b^3+c^3=21 | | 9t=-10t-3 | | -5(2x-9)=2(x-8)11 | | 20x^3+8x^2+12x= | | 4-18=z/-9 | | 12x-8=11x | | 2x^2+8x+6=8 | | 9w-8w+2=-4+2w | | 3/4c=72 | | 5j-440=30 | | 3D-10=6-5d | | -3(x-4)=-1 | | 10+c-8c=-10-3c | | 8x+12=-6x-16 | | -6(2)(-1)(-1)= | | y=niga | | 0=x^2-192X+1080 | | 6-3z=-5z-8 | | g^2-2g-8= | | 7-7q=-2q-8 | | 5y+1.5=2y-4 |